Evaluation of the enzyme activity of protozoan protein kinases by using an in vitro kinase assay. Issue 5 (October 2016) - Kato, Kentaro
Abstract: The life cycles of parasites are more complicated than those of other biological species. Protein kinases (PKs) encoded by parasites are the main triggers of life stage conversions. Phosphorylation by cellular PKs regulates important cellular processes, and the protozoan genome contains many PKs. Some PK inhibitors inhibit specific parasite life cycle event. In this report, I present a practical approach to expressing and purifying protozoan PKs by using a wheat germ cell-free protein synthesis system and I assess the phosphorylation activities of protozoan PKs by using an in vitro kinase assay. Graphical abstract: Highlights: This approach was presented to assess the activities of protozoan protein kinases. This system was established by using an in vitro kinase assay. It could be also used to calculate the activities of protein kinase inhibitors.